IMPLEMENTASI METODE TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION(TOPSIS) DALAM PEMILIHAN OBJEK WISATA - Saefurrohman, Saefurrohman; Widiyani, Rizki Cesta (Information Technology and Telematics, 2019)
Abstract Rembang Regency is a district that has developer well in various sectors, especially in the tourism sector.Departement of Culture and Tourism of Rembang Regency is making improvements in the tourism sector both in term of infrastructure, facilities and service to tourist visitor.The problem that is often experienced by visitors from cities or out-of-town visitors is to seek valid information about tourism in the Rembang Regency. Because with the development of social media, people are competing to get good pictures or baground photos. Therefore a system is designed and built that can be used to make it easier for users to know the rate of attractions and information about attractions. This Decision Making System is a web-based application created using the TOPSIS method. The design used is UML (Unied Modeling Language). For the implementation of writing using PHP and MysQL. The purpose of making this system is to make it easier for managers to determine the best tours and make it easier for visitors to find information about attractions from the best to the lowest tourist attraction.